Design and build an innovative education software or product for Microsoft Imagine Cup 2023 (B) - Tan, Bryce Jia Wei (Nanyang Technological University, 2023)
The increase in information and use of digital technology has led to new learning styles and needs that are inadequately supported by the existing learning tools and resources. In this report, we design a web application according to User Experience (UX) and User Interface (UI) Design principles, and meet technical specifications that enable the design to be ready for development. In this design process, we used a preliminary survey to gather information on user needs and create user personas. Then we made wireframes, mock ups, and prototypes, and conducted 5 rounds of prototype testing with at least 3 users each round, making further adjustments to the prototype after each round. As of the latest prototype test, we understand that the design adequately covers the key goals of this project, but there are still further additions that could improve the UX of the web application. We note these possible changes that could be made in future works to improve the web application.